Brush Licking Toxicity: Toxin & Microorganism Growth On Paint Brushes. (28th October 2020) - Hoang, C; Flaws, M; Moore, N; Lerret, N
Abstract: Introduction/Objective: A common practice utilized by painters is licking their paint brush bristles to form a sharp point for fine lines and details. Literature details artists careless around their mediums have a higher incidence of becoming ill, yet if their brushes harbor any toxic substances or pathogenic bacteria it is currently unknown. Therefore, this study aims to determine if there is risk associated with brush licking, by determining if pathogenic bacteria and/or heavy metals are present on the brushes of volunteer artists. Methods: We obtained 17 volunteer paint brushes and inoculated specialized collection and transport media (E- Swab, BD Biosciences, San Jose, CA) while the volunteer completed a qualitative de-identified survey indicating brush licking status. Brushes were swirled in the E-swab collection tube, then subbed to sheep blood agar plates and chocolate agar plates for bacteria growth analysis. Matrix-assisted laser desorption/ionization time-of-flight (MALDI- TOF) technology was used for identification. With the remaining E-Swab media, lead (3M, St. Paul, MN) and arsenic (HACH, Loveland, CO) testing using commercial kits was done. MALDI-TOF identification and heavy metal testing results were then compared to survey results. Results: One of 17 specimens (6%) had pathogenic bacteria identified (Pseudomonas aeruginosa). This specimen's survey also indicated routine brush licking. The sensitivity and specificity of MALDI-TOF for Pseudomonas aeruginosa is 96.67% and 97.87%, respectively. The remaining 16/17 (94%) had normal flora present. Importantly, the specimen containing Pseudomonas aeruginosa also had high levels of arsenic at 50 ppb. None of the specimen tested contained lead. Conclusion: Our results indicated there is indeed some risk associated with brush licking. However, due to the small sample size, statistical significance could not be determined. Nonetheless, with the lack of knowledge surrounding this subject, it is beneficial to further explore and educate painters on the toxicities of brush licking.